Cryopreservation of tench, Tinca tinca, sperm: Sperm motility and hatching success of embryos - Rodina, M; Gela, D; Kocour, M; Alavi, S M Hadi; Hulak, M; Linhart, O (Theriogenology, 2007)
The aim of the present study was to elaborate cryopreservation methods for ex situ conservation of tench. Success of cryopreservation was tested during two series of experiments. The first set of experiments studied the effects of two types of cryoprotectants (DMSO and a combination of DMSO with propanediol at ratio 1:1) at concentrations of 8 and 10% and three different equilibration times in two different immobilization solutions (IS) (Kurokura 180 and Kurokura) before freezing (0.0, 2.0 and 4.0h after T(0)). The K4 cooling programme was used to freeze 1ml of cryoextended sperm using 1.8ml cryotubes. Main monitored parameter was hatching rate after using of cryopreserved sperm. The second set of experiments studied the volume effect of 0.5, 1 and 5ml straws and compared these with 1.8ml cryotubes as well as the effect of the cooling programme (K4 and L1). Following the results of the first study, a combination of DMSO and propanediol (ratio 1:1) at concentration of 10% was added to extended sperm in Kurokura 180 IS. Main monitored parameter was hatching rate after using cryopreserved sperm, supplementary parameters were sperm velocity and motility percentage assessed at 10s post-activation. Sperm was collected directly into IS and stored at 4 degrees C for 2.5h. Thereafter were sperm samples pooled, equlibred in IS (first set of experiments) or directly mixed with cryoprotectants (DMSO or a mixture of DMSO with propanediol at ratio 1:1) and transferred to 1.8ml cryotubes or straws (0.5, 1 and 5ml). Then the cryotubes/straws were directly transferred to pre-programmed PLANER Kryo 10 series III and cooled using two different cooling programmes including a slow cooling programme (a) named K4 (from +4 to -9 degrees C at a rate of 4 degrees Cmin(-1) and then from -9 to -80 degrees C at a rate of 11 degrees Cmin(-1)) and a rapid cooling programme (b) named L1 (directly from +4 to -80 degrees C at a rate of 20 degrees Cmin(-1)). Both slow (K4) and rapid (L1) cooled samples were held 6min at -80 degrees C. Finally, samples were transferred into liquid N(2). The frozen spermatozoa were thawed in a water bath (40 degrees C) according to the frozen volume and checked for fertilization and hatching rates. Percentage of sperm motility and sperm velocity were measured using video recorded frames. ANOVA showed a significant influence of frozen and fresh sperm in all treatments. The hatching rates of 33.8% were obtained when sperm was equilibrated for 0h before freezing in IS of Kurokura 180 and frozen with a 10% of mixture 1:1 of DMSO and propanediol into straws of 5ml and cooled using program L1. The velocity of frozen-thawed spermatozoa ranged from 31 to 46microms(-1) and in post-thawed sperm was not significantly different according to frozen sperm volume, but a higher velocity was obtained when sperm was fast frozen using programme L1. A large volume of frozen sperm could reveal the best procedure for freezing, but also for simulating methods of artificial propagation for future practical use of frozen tench sperm at a large scale.
Keywords: uchování spermatu; Cryopreservation; Cyprinidae; počet spermií; Semen Preservation; propylenglykoly; dimethylsulfoxid; Female; Embryonic Development; Dimethyl Sulfoxide; Sperm Motility; kryoprezervace; Fertilization in Vitro; motilita spermií; kryoprotektivní látky; mužské pohlaví; fertilizace in vitro; Cryoprotective Agents; Propylene Glycols; zvířata; ženské pohlaví; Animals; Male; Sperm Count; embryonální vývoj